Erythrocyte and iron profiles in soil-transmitted helminth-infected children in a rural area in Banten, Indonesia - Sungkar, Saleha; Sukartini, Ninik; Wirastuti, Aulia; Tanjungsari, Dian Wahyu (Medical Journal of Indonesia, 2024)
BACKGROUND Soil-transmitted helminth (STH) infection, frequently caused by Ascaris lumbricoides, Trichuris trichiura, and hookworms (Ancylostoma duodenale and Necator americanus), often gives rise to malabsorption of nutrients that form hemoglobin (Hb) thereby causing anemia. This study aimed to know the difference in erythrocyte profile in children with and without STH infections. METHODS This cross-sectional study involved 205 children from two Panimbang Jaya elementary schools in Pandeglang, Banten, Indonesia. Blood and stool samples were collected from a previous study conducted from November 2021 to May 2022. Erythrocyte parameters were Hb concentration, erythrocyte count, mean corpuscular volume (MCV), mean corpuscular Hb (MCH), and red cell distribution width (RDW). The iron profile included serum iron, total iron-biding capacity (TIBC), and ferritin. Worm infestation was detected by direct stool microscopical examination. Statistical analysis was performed using SPSS software version 20. RESULTS The prevalence of STH infection in Pandeglang was 44.4%, primarily characterized by mild intensity STH infection (79%). The identified STH species were A. lumbricoides, T. trichiura, and combination of both. The median differences between erythrocyte count, MCV, and MCH, and the mean differences of TIBC and serum iron were not statistically significant (p = 0.388, 0.098, and 0.057, and p = 0.304 and 0.455). However, children with STH infection had lower Hb (12.57 versus 12.95 g/dl) and ferritin (19.60 versus 30.57 µg/dl) levels but higher RDW (13.20 versus 13.10%). CONCLUSIONS A high prevalence of STH infection was identified among schoolchildren, but their erythrocyte profiles were similar regardless of STH infection status.